Investigation and diagnostics of plasma flows in a pulsed plasma accelerator for experimental modelling of processes in tokamaks - M. K. Dosbolayev; A. B. Tazhen; T. S. Ramazanov (Eurasian Journal of Physics and Functional Materials, 2021)
This paper presents the experimental results on electron, ion temperatures and densities in a pulsed plasma accelerator. The values of electron densities and temperatures were computed using the methods of relative intensities of Hα and Hβ lines, Hβ Stark broadening, and the technique is based on Faraday cup beam current measurements. In this work, a linear optical spectrometer S-100 was used to acquire the emission spectra of hydrogen and air plasmas. In this spectrum, there are some lines due to Fe, Cu, N2, O2, and H2. The series of visible lines in the hydrogen atom spectrum are named the Balmer series. The spectral emissions of iron and copper occur throughout the gas breakdown and ignition of an arc discharge, during the erosion and sputtering of materials. The vacuum chamber and coaxial electrodes were made. The electron temperatures and densities in a pulsed plasma accelerator, measured via relative intensities of spectral lines and Stark broadening, at a charging voltage of a capacitor bank of 3 kV and a working gas pressure in a vacuum chamber of 40 mTorr, were 2.6 eV and 1.66 · 1016 cm−3 for hydrogen plasma. These results were compared with the Faraday cup beam current measurements. However, no match was found. Considering and analyzing this distinction, we concluded that the spectral method of plasma diagnostics provides more accurate results than electrical measurement. The theory of probe measurements can give approximate results in a moving plasma.